THE EFFECTIVNESS OF CANVA IN PROJECT BASED LEARNING TO INCREASE STUDENT WRITING SKILL - Faqih, Moch.; Waode Hamsia, Waode Hamsia; Roi'fah, FNU (TELL - US JOURNAL, 2023)
This study aims to determine the effectiveness of the usage of the Canva media utility to enhance students' writing abilties. Researchers used a quantitative method that's a pre-experimental research design by making use of pre-test and post-test.  Written exams are used to gather scholar fulfillment as an tool of this studies. The researchers used two classes in the 9th grade of junior high school as research samples. Dedication of the sample of this have a look at the use of random sampling method.  To investigate studies facts, researchers used the t-test.  Primarily based at the studies evaluation, the common score of the students' writing take a look at for the remedy magnificence in the post-test changed into (85.25), and the pre-test turned into (65.50).  For the non-treatment class (61.00) for the pre-test at consequences.  For the post-test only got (61.25).  The effects also show that the T-test fee (9.185) is better than desk (1.824), at a significance degree of 5%.  If the t-test a look at consequences are better than the t-desk.  It suggests that the alternative hypothesis (Ha) was accepted and (Ho) was rejected. Primarily based at the consequences of t-test calculations, it has a look at can be concluded that the Canva utility is an powerful medium for facilitating students in improving their writing performance of descriptive text.  For similarly examine, English teacher can apply as the basic principle in this study as a attention for teaching writing capabilities. And will be a benefit later for the future.